PATTERNS OF DEPRESSION, ANXIETY SYMPTOMS AND COPING STYLES AMONG EARLY AND LATE ADOLESCENT STUDENTS: Depression, Anxiety Symptoms and Coping Styles - Yaqoob, Naila; Khan, Masha Asad (Pakistan Armed Forces Medical Journal, 2014)
Objective: To compare the depression, anxiety symptoms and coping styles among early and late adolescent students.Study Design: Cross-sectional.Place and Duration of study: Study was carried out at University of the Punjab, Lahore from 17 February to 31st August 2010.Methods: A purposive sample of 600 students (boys=300; girls=300) was divided into two age groups; early adolescents (13-15 years) and late adolescents (16-18 years). Participants were administered beck anxiety inventory, beck depression inventory-II and coping strategies questionnaire. Data was analyzed on SPSS 14 version using independent sample t test.Results: The overall results of the study indicated that early adolescents exhibit more depression and anxiety symptoms as compared to the late adolescents. Moreover, early and late adolescents each attempt to cope with stressors in a variety of ways as active practical coping styles were more utilized by late adolescents. On the other hand, religious focused and avoidance focused coping styles were mostly used by the early adolescents. Besides, there was no significant group difference on active distractive coping styles.Conclusion: The current study revealed that significant changes during adolescence may affect adaptive processes and have implications for intervention efforts aimed to reduce the negative effects of stress during this period. The findings also suggest early and late adolescents each attempt to cope with stressors in a variety of ways that become more diverse and adaptive with development through the adolescent years.